Aboriginal Liaison and Cross-Cultural Matters: The Role of the Northern Territory Department of Mines and Energy - K Whelan (The Australasian Institute of Mining and Metallurgy, 1994)
The Land Access Branch of the Mines Division of the Northern Territory Department of Mines and Energy is responsible for Aboriginal Liaison and cross-cultural matters that affect the Department. In essence, it exists to provide a basis for communication between the Department, industry. Aboriginal organisations and Traditional Owners. The paper outlines the various ways in which this is accomplished including the preparation of detriment submissions for pending land claim hearings, the use of promotional material to support access to Aboriginal Land for NTGS Mapping Programs and field work, and advice/assistance on exploration and mining issues.